A Preliminary Study of Blastocystis sp. Isolated from Chicken in Perak And Selangor, Malaysia - M. T., Farah Haziqah; P., Chandrawathani; S.N., Mohd Zain; G., Suresh Kumar; C., Hemalatha; B., Premaalatha (Department of Veterinary Services Malaysia, 2014)

(untitled)
ABSTRACT. Blastocystis is considered to be a zoonoses and it is believed that animals such as chicken constitute large reservoirs for human infection via the faecal-oral route. Therefore, Blastocystis infection was surveyed in free-range chicken and cagereared chicken comprising broiler birds for consumption as well as jungle fowls and silkie chicken kept for recreation. Fresh faecal samples collected were examined by wet smear preparation and were cultured in Jones medium supplemented with 10% horse serum. Out of 107 chickens, it was found that most of the free-range chicken was positive for Blastocystis sp. with a high prevalence rate of 80%–100% in village chicken, jungle fowl and white silkie chicken. However, the cage-reared chicken, consisting of broiler chicken had no infection. The vacuolar form was the most common Blastocystis cell form found in cultures, similar to B. hominis. These cells were usually spherical and vary greatly in size, ranging from 10 μm to 30 μm in diameter. Owing to the free ranging and scavenging habits, the likelihood of acquiring the infection from the environment contaminated with the faecal material of animals with Blastocystis is high in free-range chicken as compared to caged chicken.